2015
DOI: 10.1111/liv.12979
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia is associated with severity of cirrhosis and negative impact after liver transplantation

Abstract: Hyperhomocysteinemia is frequently present in patients with cirrhosis and is associated with severe liver disease and reduced graft and patient survival after liver transplantation. The negative impact hyperhomocysteinemia has on graft and patient survival is not related to thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In addition, among the patients with liver cirrhosis, the severity of liver disease is often in parallel with the prevalence of HHcy. 18,21 Similarly, the present study found that patients with Child-Pugh class B/C had a higher proportion of HHcy, and Child-Pugh score positively correlated with HHcy.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, among the patients with liver cirrhosis, the severity of liver disease is often in parallel with the prevalence of HHcy. 18,21 Similarly, the present study found that patients with Child-Pugh class B/C had a higher proportion of HHcy, and Child-Pugh score positively correlated with HHcy.…”
Section: Discussionsupporting
confidence: 77%
“…A previous study 25 found that the mean plasma Hcy concentration was elevated in liver cirrhosis patients than in the control group. A recent study 26 found an association between HHcy and the severity of liver cirrhosis, and HHcy was related to a lower survival rate in patients post-liver transplantation. Additionally, animal experiments revealed that HHcy promoted LF in mice by activating the aromatic hydrocarbon receptor/CD36 pathway.…”
Section: Discussionmentioning
confidence: 96%
“…That working hypothesis should be confirmed by the demonstration of a negative correlation between rising Hcy values and declining TTR plasma levels [ 25 , 26 ] in aged subjects. The liver may similarly endure toxic exposure and varying inflammatory, autoimmune, and degenerative processes associated with HHcy states, as described in viral hepatitis [ 62 ], cirrhosis [ 63 ], and nonalcoholic steatosis [ 64 ]. The replacement of normal parenchymal cells by fatty, fibrotic, or inflammatory material would lead to marked intrahepatic dysregulation of Met metabolism, as recently documented in mouse experiments showing that diet-induced steatofibrosis is associated with HHcy status and a 30% depletion of the intrahepatic Met pool size [ 65 ].…”
Section: Salvage Mechanisms For Methionine Homeostasismentioning
confidence: 99%